Efektivitas Penggunaan Strategi Pembelajaran Peer Lesson Berbasis Pendekatan Saintifik Terhadap Kemampuan Bertanya Siswa Dalam Pembelajaran Sejarah - Afdar*, Muhammad; Mawardi, Mawardi; Kesuma, Teuku Bahagia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to determine students' questioning abilities by using peer lesson learning strategies based on a scientific approach in history learning at SMA Negeri 1 Peudada. The approach used in this research is a qualitative approach with a qualitative descriptive research type. The research subjects were determined using a purposive sampling technique as many as 34 students. The data collection technique used is observation. Based on the research results, the percentage of clarity of questions submitted by students was obtained at a percentage of 75% and included in the good category, for the indicator of clarity of the relationship between students' questions and the problem being discussed, the percentage was obtained at 75% and included in the good category, for the indicator of providing time to think for asking and answering obtained a percentage of 87.5% and was included in the very good category, in the indicator of distributing questions evenly among the students the percentage was obtained at 75% and included in the good category, and in the indicator of giving question demands the percentage was obtained at 41.6 % and is included in the poor category. Based on the results of data analysis, it was concluded that the peer lesson learning strategy based on a scientific approach had a positive effect on students' ability to ask questions.